1968
DOI: 10.1111/j.1469-7998.1968.tb03031.x
|View full text |Cite
|
Sign up to set email alerts
|

The walking gaits of some species of Pecora

Abstract: A method is presented for defining the walking gaits of quadrupeds from films so that they can be compared in closely related species. Differences in walking patterns of 18 pecoran species belonging to four families are discussed with respect to anatomy and environment. Variation in the walk patterns of members within a species are assessed. They are found to vary often with the speed at which the walk is executed, with the terrain, with the presence of heavy horns or antlers and with age. The time taken for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

1973
1973
2019
2019

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…Giraffes appear to diverge from the predictions of dynamic similarity at faster than walking speeds. Instead of using an intermediate speed gait, such as a trot, giraffes seemingly transition consistently from a walk to a rotary gallop (Dagg & Vos 1968;Maxwell 1924). The restricted choice of gait is in contrast to most other cursorial quadrupeds (Heglund & Taylor 1988;Hildebrand 1976), but not exclusive to giraffes; for example elephants use the lateral sequence walk across their entire speed range (Hutchinson et al 2006).…”
Section: Eqn 1 = 2 ℎmentioning
confidence: 99%
“…Giraffes appear to diverge from the predictions of dynamic similarity at faster than walking speeds. Instead of using an intermediate speed gait, such as a trot, giraffes seemingly transition consistently from a walk to a rotary gallop (Dagg & Vos 1968;Maxwell 1924). The restricted choice of gait is in contrast to most other cursorial quadrupeds (Heglund & Taylor 1988;Hildebrand 1976), but not exclusive to giraffes; for example elephants use the lateral sequence walk across their entire speed range (Hutchinson et al 2006).…”
Section: Eqn 1 = 2 ℎmentioning
confidence: 99%
“…From the study of locomotor behaviour, much is known about the gait patterns, footfall sequences, timing, speed, and support patterns for a wide variety of vertebrate species (e.g. Dagg, 1973;Dagg & de Vos, 1968;Hildebrand, 1959Hildebrand, , 1965Hildebrand, , 1967Hildebrand, ,1968Howell, 1965;Zug, 1972). However, little is known about changing gait behaviour as an animal matures.…”
Section: Introductionmentioning
confidence: 99%
“…A study involving simulations of quadrupedal gaits also suggested that giraffes will select a pacing gait at intermediate speeds (Suzuki et al 2016); however this model inaccurately predicted that giraffes use a diagonal sequence walk at slow speeds, contrasting with the experimentally observed lateral sequence walk (Basu et al 2018). Giraffes instead seemingly transition consistently from a walk to a rotary gallop (Dagg & Vos 1968;Maxwell 1924). The restricted choice of gait is in contrast to most other cursorial quadrupeds (Heglund & Taylor 1988;Hildebrand 1976), but not exclusive to giraffes; for example elephants use the lateral sequence walk across their entire speed range (Hutchinson et al 2006).…”
Section: Eqn 1 = 2 ℎmentioning
confidence: 99%